Visceral artery aneurysms: an institutional review - Rajan Sapkota (Society of Surgeons of Nepal, 2017)
Methods: It is a retrospective review of prospectively kept data of patients treated for visceral artery aneurysms in Tribhuvan University Teaching Hospital and Manmohan Cardiothoracic Vascular and Transplant Center from 1997 to 2009.